Evaluasi Kapasitas Ruas Jalan Menggunakan Metode Mkji 1997 Dan PKJI 2023 Pada Jalan Kl. Yos Sudarso Kota Medan - Hutahaean, Anggi S; Lubis, Kamaluddin (Universitas Sulawesi Tenggara, 2025)
Kl. Yos Sudarso street Medan can be said to be an arterial road in the city of Medan which has a fairly high vehicle volume. Along this section of road there are several businesses and houses belonging to the community, causing a pile up of vehicles on this section of road. The purpose of this research is to analyze the extent of road capacity capacity on Jalan Kl. Yos Sudarso, West Medan District, Medan City accommodates the volume of vehicles. Yos Sudarso. This research uses the MKJI and PKJI methods so that using the 1997 MKJI method the capacity values for each segment are obtained as follows: Road capacity is 1698.84 pcu/hour Free flow speed of the KL road section. Yos Sudarso is 57.57 km/hour Degree of Saturation on KL roads. Yos Sudarso was 6,867. Meanwhile, based on the results of data analysis on field conditions using the PKJI 2023 method, the capacity values for each segment were obtained as follows: Road capacity is 1750, 32 pcu/hour. Free flow speed of the KL road section. Yos Sudarso of 59.59 km/hour Degree of Saturation of KL roads. Yos Sudarso of 8.844 Based on the results of the MKJI 1997 and PKJI 2023 methods, the resulting values of capacity, free flow speed and degree of saturation are different and there are differences in the notation and units in the adjustment factors.